Paper Strengthening Agent and Paper

By using a specific composition of (meth)acrylamide-based polymer, water-soluble aluminum compound, inorganic acid and inorganic acid in the paper force enhancer, the increase in viscosity and poor storage stability of paper force enhancer in the prior art is solved. The problem is that excellent paper force effect and stability in papermaking are achieved.

CN114541172BActive Publication Date: 2024-12-20ARAKAWA CHEM IND LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111358626.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-18
Filing Date
2021-11-16
Publication Date
2024-12-20
Estimated Expiration
2041-11-16

AI Technical Summary

Technical Problem

The viscosity of existing paper force enhancers increases over time, resulting in poor storage stability and it is difficult to effectively exert paper force effect during papermaking.

Method used

Using a mixed solution containing (meth)acrylamide-based polymer, water-soluble aluminum compound, inorganic acid salt and inorganic acid, a paper force enhancer with excellent storage stability and paper force effect is formed by adjusting the molar ratio and additive composition. .

Benefits of technology

The viscosity of the paper force enhancer is inhibited from increasing over time, significantly improving the paper force effect of the paper, and maintaining good stability during the papermaking process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003357822230000141
    Figure BDA0003357822230000141
  • Figure BDA0003357822230000171
    Figure BDA0003357822230000171
Patent Text Reader

Abstract

The present invention provides a paper strengthening agent and paper, wherein the paper strengthening agent has excellent storage stability and exhibits a good paper strengthening effect when made into paper. A paper strengthening agent, which is a mixed solution containing a (meth)acrylamide polymer (A), a water-soluble aluminum compound (B), an inorganic acid salt (C) (the (C) component excluding the (B) component) and an inorganic acid (D), wherein the (meth)acrylamide polymer (A) contains (meth)acrylamide (a1), a polymerizable monomer having a cationic group (a2), a polymerizable monomer having an anionic group (a3) ​​and a crosslinking monomer (a4) as reaction components; when the viscosity of the mixed solution just prepared (concentration 15 weight %, temperature: 25°C) is X1 mPa·s, and the viscosity of the mixed solution after being stored at a temperature of 60°C for 3 days (concentration 15 weight %, temperature: 25°C) is X2 mPa·s, 30≤X1≤30,000 and 0.8≤X2 / X1≤2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a paper strengthening agent and paper obtained by using the same. Background Art

[0002] Paper strength agents are chemicals used to increase the strength of paper itself. In particular, as the papermaking system in the papermaking industry is becoming more closed (such as recycling waste paper pulp), the strength of the pulp fiber used as the raw material is reduced, which makes it easy for the strength of the resulting paper to further decrease. In such an environment, the importance of paper strength agents is increasing.

[0003] By the way, (meth)acrylamide polymers are widely used as paper strengthening agents, and are classified into anionic, cationic and amphoteric types according to their ionicity. Among them, the mainstream amphoteric (meth)acrylamide polymers are obtained by copolymerizing acrylamide with a polymerizable monomer such as a cationic monomer or an anionic monomer (Patent Document 1).

[0004] When the polymer is added to the pulp slurry of the papermaking system, aluminum sulfate is also added as a fixing agent, but the fixing effect of aluminum sulfate decreases as the papermaking system becomes closed. In addition, from the perspective of environmental load, there is a trend to reduce the amount of aluminum sulfate added in papermaking plants, and the paper strength effect of the paper strengthening agent itself is difficult to further exert, which has become a problem. As a solution to this problem, a method of adding a paper strengthening agent that mixes a (methyl)acrylamide polymer with a water-soluble aluminum compound such as aluminum sulfate is known (Patent Document 2). Such a mixed paper strengthening agent has advantages such as reducing the amount of aluminum sulfate added to the pulp slurry and improving the paper strength effect.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-251252

[0008] Patent Document 2: Japanese Patent Application Publication No. 2001-011787

[0009] However, a paper strengthening agent containing both a (meth)acrylamide polymer and a water-soluble aluminum compound mainly forms a crosslinked structure in which a plurality of polymer ions are bonded to aluminum atoms (hereinafter referred to as "metal crosslinks") through electrostatic interaction between anionic groups in the polymer and cationic aluminum atoms. As a result, the paper strengthening agent is prone to thickening over time, which is a problem in terms of so-called storage stability. Summary of the invention

[0010] Problems to be solved by the invention

[0011] An object of the present invention is to provide a paper strengthening agent having excellent storage stability and exhibiting a good paper strength effect in paper.

[0012] Means for solving problems

[0013] The present inventors have conducted intensive studies on the components contained in a paper strengthening agent, and as a result, have found a solution to the above-mentioned problems, thereby completing the present invention. Specifically, the present invention relates to the following paper strengthening agent and paper.

[0014] 1. A paper strengthening agent, which is a mixed solution comprising a (meth)acrylamide polymer (A), a water-soluble aluminum compound (B), an inorganic acid salt (C) (component (C) excluding component (B)), and an inorganic acid (D), wherein the (meth)acrylamide polymer (A) comprises (meth)acrylamide (a1), a polymerizable monomer having a cationic group (a2), a polymerizable monomer having an anionic group (a3), and a crosslinking monomer (a4) as reaction components;

[0015] When the viscosity of the just-prepared mixed solution (concentration 15 wt %, temperature: 25°C) is set to X1 mPa.s, and the viscosity of the mixed solution (concentration 15 wt %, temperature: 25°C) after being stored at 60°C for 3 days is set to X2 mPa.s, 30≤X1≤30,000 and 0.8≤X2 / X1≤2.

[0016] 2. The paper strengthening agent according to item 1 above, wherein the molar ratio of the reaction components is: 55 mol% to 98 mol% of component (a1), 0.5 mol% to 20 mol% of component (a2), 0.5 mol% to 20 mol% of component (a3), and 0.002 mol% to 2 mol% of component (a4).

[0017] 3. The paper strengthening agent according to 1 or 2 above, wherein the component (B) is aluminum sulfate and / or a hydrate thereof.

[0018] 4. The paper strengthening agent according to any one of 1 to 3 above, wherein the content of the component (B) is 0.3 to 20 parts by weight as aluminum ions based on solid content weight per 100 parts by weight of the component (A).

[0019] 5. The paper strengthening agent according to any one of 1 to 4 above, wherein the component (C) comprises one or more selected from the group consisting of sodium phosphate, potassium phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, sodium sulfate, potassium sulfate, sodium hydrogen sulfate, and potassium hydrogen sulfate.

[0020] 6. The paper strengthening agent according to any one of 1 to 5 above, wherein the content of the component (C) is 1 to 70 parts by weight based on solid content weight relative to 100 parts by weight of the component (A).

[0021] 7. The paper strengthening agent according to any one of 1 to 6 above, wherein the component (D) is sulfuric acid and / or phosphoric acid.

[0022] 8. The paper strengthening agent according to any one of 1 to 7 above, wherein the pH of an aqueous solution having a solid content concentration of 1% by weight is 2 to 3.5 at a temperature of 25°C.

[0023] 9. Paper obtained by using the paper strengthening agent according to any one of 1 to 8 above.

[0024] Effects of the Invention

[0025] The paper strength enhancer of the present invention can suppress the increase of viscosity over time and exhibit excellent paper strength effect in paper. DETAILED DESCRIPTION

[0026] The paper strengthening agent of the present invention is a mixed liquid containing the following substances: a (meth)acrylamide polymer (A) (hereinafter referred to as component (A)), a water-soluble aluminum compound (B) (hereinafter referred to as component (B)), an inorganic acid salt (C) (excluding those belonging to component (B) in component (C)) (hereinafter referred to as component (C)), and an inorganic acid (D) (hereinafter referred to as component (D)).

[0027] The component (A) is a component that exerts an excellent paper strength effect. In the present invention, it refers to a polymer containing (meth)acrylamide (a1) (hereinafter referred to as the component (a1)), a polymerizable monomer (a2) having a cationic group (hereinafter referred to as the component (a2)), a polymerizable monomer (a3) ​​having an anionic group (hereinafter referred to as the component (a3)), and a crosslinking monomer (a4) (hereinafter referred to as the component (a4)) as reaction components. Here, the polymerizable monomer refers to a monomer having one or more double bonds and / or carbon-carbon triple bonds in one monomer molecule.

[0028] Examples of the component (a1) include methacrylamide and acrylamide, which may be used alone or in combination of two or more.

[0029] The component (a2) is not particularly limited as long as it has a cationic group, and various known components can be used. Examples thereof include polymerizable monomers having secondary amino groups, polymerizable monomers having tertiary amino groups, and quaternary salts of these polymerizable monomers.

[0030] There are no particular limitations on the polymerizable monomers having secondary amino groups, and examples thereof include diallylamine, etc. There are no particular limitations on the polymerizable monomers having tertiary amino groups, and examples thereof include (meth)acrylates having tertiary amino groups such as N,N-dimethylaminoethyl (meth)acrylate and N,N-diethylaminoethyl (meth)acrylate; (meth)acrylamides having tertiary amino groups such as N,N-dimethylaminopropyl (meth)acrylamide and N,N-diethylaminopropyl (meth)acrylamide. The quaternary salts of these monomers refer to substances obtained by reacting the polymerizable monomers having the above-mentioned secondary amino groups or the polymerizable monomers having tertiary amino groups with a quaternizing agent, etc. As quaternary salts, inorganic acid salts such as hydrochlorides and sulfates may be used, or organic acid salts such as acetates may be used. In addition, methyl chloride, benzyl chloride, dimethylsulfuric acid, epichlorohydrin, etc. may be used as quaternizing agents. These may be used alone or in combination of two or more. Among them, polymerizable monomers having a tertiary amino group and / or quaternary salts thereof are preferred, (meth)acrylates having a tertiary amino group and / or quaternary salts thereof are more preferred, N,N-dimethylaminoethyl (meth)acrylate and quaternary salts of N,N-dimethylaminoethyl (meth)acrylate are further preferred, and N,N-dimethylaminoethyl acrylate, N,N-dimethylaminoethyl acrylate benzyl chloride, and methacrylate N,N-dimethylaminoethyl benzyl chloride are particularly preferred. It should be noted that "(meth)acrylate" refers to methacrylate or acrylate.

[0031] As the (a3) ​​component, there is no particular limitation as long as it is a component having an anionic group, and various known components can be used. For example, (meth) acrylic acid, itaconic acid, itaconic anhydride, fumaric acid, maleic acid and other polymerizable monomers having a carboxyl group; vinyl sulfonic acid, methallyl sulfonic acid and other polymerizable monomers having a sulfonic acid group, etc. can be listed. It should be noted that these (a3) ​​components can be used in the form of salts such as alkali metal salts such as sodium and potassium, ammonium salts, etc. These can be used alone or in combination of two or more. Among them, (meth) acrylic acid, itaconic acid, and sodium methallyl sulfonate are preferred.

[0032] The component (a4) is a component for introducing a branched structure into the polymer. The component (a4) is not particularly limited, and examples thereof include N-alkyl (meth)acrylamides such as N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, and N-tert-butyl (meth)acrylamide; N,N-dialkyl (meth)acrylamides such as N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and N,N-diisopropyl (meth)acrylamide; and N,N′- N,N′-alkylenebis(meth)acrylamide such as methylenebis(meth)acrylamide and N,N′-ethylenebis(meth)acrylamide; crosslinking monomers having a triallyl group such as triallyl isocyanurate, triallyl trimellitate, triallylamine, triallyl(meth)acrylamide; triazines having a (meth)acryloyl group such as 1,3,5-triacryloyl-1,3,5-triazine and 1,3,5-triacryloylhexahydro-1,3,5-triazine. These can be used alone or in combination of two or more. Among them, at least one selected from the group consisting of N,N-dialkyl(meth)acrylamide, N,N′-alkylenebis(meth)acrylamide and triazines having a (meth)acryloyl group is preferred, and N,N-dimethylacrylamide and N,N′-methylenebisacrylamide are more preferred.

[0033] The amount of each reaction component used is not particularly limited, but is set as follows in terms of molar ratio from the viewpoint that the obtained paper exhibits excellent paper strength.

[0034] Component (a1): preferably 55 to 98 mol%, more preferably 77.8 to 93.5 mol%

[0035] Component (a2): preferably 0.5 to 20 mol%, more preferably 3 to 10 mol%

[0036] Component (a3): preferably 0.5 to 20 mol%, more preferably 1 to 10 mol%

[0037] Component (a4): preferably 0.002 to 2 mol%, more preferably 0.004 to 0.5 mol%

[0038] As the above-mentioned reaction components, monomers (a5) other than components (a1) to (a4) (hereinafter referred to as component (a5)) may also be included. Component (a5) is not particularly limited, and examples thereof include polymerizable monomers having aromatic rings such as styrene, α-methylstyrene, and vinyltoluene; alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate; vinyl carboxylates such as vinyl acetate and vinyl propionate; nitriles such as acrylonitrile; thiols such as 2-mercaptoethanol and n-dodecyl mercaptan; alcohols such as ethanol, isopropanol, and n-pentanol; aromatic compounds such as α-methylstyrene dimer, ethylbenzene, isopropylbenzene, and isopropylbenzene; carbon tetrachloride, etc. These may be used alone or in combination of two or more. In addition, the content of component (a5) is less than 5 mol% in all the constituent monomers.

[0039] In the manufacture of the polymer, for the purpose of adjusting the pH of the above-mentioned monomer solution, inhibiting the hydrolysis of the monomer (polymerization stabilization), etc., organic acids such as citric acid, succinic acid, and oxalic acid; inorganic acids such as hydrochloric acid, sulfuric acid, and phosphoric acid; inorganic bases such as sodium hydroxide, potassium hydroxide, and calcium hydroxide; additives such as defoamers and antioxidants may be added. These may be used alone or in combination of two or more, and their content is preferably 15 parts by weight or less, and more preferably 10 parts by weight or less, relative to 100 parts by weight of all constituent monomers.

[0040] The component (A) is not particularly limited and can be obtained by polymerizing monomer components including the components (a1), (a2), (a3) ​​and (a4), and optionally the component (a5) and the above-mentioned additives in a solvent.

[0041] The polymerization method is not particularly limited, and examples thereof include a method using only a dropping polymerization method, and a method combining a simultaneous polymerization method (adding a monomer mixed solution all at once) and a dropping polymerization method.

[0042] The dropwise polymerization method is a method of dropping a monomer mixture into a reaction system in which a solvent such as water has been added in advance. As methods using only this polymerization method, for example, the following (1) to (3) can be cited. It should be noted that the dropwise addition can be continuous, or the dropwise addition can be stopped midway and then the polymerization is allowed to proceed after a certain period of time.

[0043] (1) Method of dripping a monomer mixture solution containing all monomer components

[0044] (2) Method of preparing two or more monomer mixed solutions separately and then adding them dropwise simultaneously

[0045] (3) Method of preparing two or more monomer mixed solutions and then adding them dropwise in sequence

[0046] In addition, examples of the method of combining the simultaneous polymerization method and the dropping polymerization method include the following (4) to (7).

[0047] (4) A method of simultaneously polymerizing the monomer mixtures and then mixing the polymers

[0048] (5) A method of adding the remaining monomer mixture dropwise after completing simultaneous polymerization of one or more monomer mixtures

[0049] (6) A polymerization method in which the remaining monomer mixture is added dropwise during simultaneous polymerization of one or more monomer mixtures

[0050] (7) A method of performing dropwise polymerization of one or more monomer mixtures, and then adding the remaining monomer mixtures together to perform simultaneous polymerization

[0051] Here, when preparing two or more monomer mixtures, it is more preferred to perform an operation to increase the concentration of the components (a2) and (a3) ​​involved in the reaction in any one of the monomer mixtures: increasing the amounts of the components (a2) and (a3) ​​in a part of the mixture and allowing these mixtures to react in sequence, or adding the components (a2) and (a3) ​​at a certain point in time during the polymerization reaction.

[0052] As the solvent, water, organic solvents, etc. can be cited, which can be used alone or in combination of two or more. As the organic solvent, there is no particular limitation, and examples thereof include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, isobutanol, n-hexanol, n-octanol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, and diacetone alcohol; and ethers such as ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether. Among them, water is usually preferably used from the viewpoint of dissolving components (a1) to (a5).

[0053] The polymerization initiator is not particularly limited, and examples thereof include persulfates such as ammonium persulfate, potassium persulfate, and sodium persulfate; azo compounds such as 2,2′-azobis(2-amidinopropane) hydrochloride, 2,2′-azobis[2(2-imidazoline-2-yl)propane] hydrochloride; hydrogen peroxide, etc. These may be used alone or in combination of two or more. Among them, from the viewpoint of allowing solution polymerization to proceed sufficiently, ammonium persulfate, potassium persulfate, and 2,2′-azobis(2-amidinopropane) hydrochloride are preferred. In addition, there is no particular limitation on the method for adding the polymerization initiator, and it may be appropriately selected to add all at once, add in batches, or add continuously. In addition, the content of the polymerization initiator is also not particularly limited, and is generally about 0.001 to 5 parts by weight, preferably about 0.01 to 1 part by weight, relative to 100 parts by weight of components (a1) to (a5).

[0054] The polymerization conditions are not particularly limited, but for example, the temperature is about 50 to 100° C. and the time is about 1 to 8 hours.

[0055] The physical properties of the obtained component (A) include, for example, a weight average molecular weight of usually 500,000 to 7,000,000, and preferably 1,000,000 to 6,000,000, from the viewpoint of fixation to pulp and the effect of improving paper strength. The "weight average molecular weight" herein refers to a value obtained by gel permeation chromatography (GPC).

[0056] The viscosity of component (A) is usually 500 to 150,000 mPa·s, preferably 1,500 to 100,000 mPa·s. The "viscosity" herein refers to the value measured by a B-type viscometer using a solution having a solid content concentration of 15 wt % and adjusted to 25° C. (the same applies hereinafter).

[0057] Component (B) is a water-soluble aluminum compound, which is a component that promotes the excellent paper strength effect of paper by metal cross-linking through electrostatic interaction with component (A). Component (B) includes, for example, aluminum sulfate, aluminum chloride, basic aluminum sulfate, basic aluminum chloride, aluminum silicate, polyaluminum chloride, polyaluminum hydroxide, etc. It should be noted that component (B) can use hydrates. These can be used alone or in combination of two or more. Among them, aluminum sulfate, aluminum chloride, polyaluminum chloride are preferred, and aluminum sulfate is more preferred, based on ease of availability.

[0058] The content of the component (B) is not particularly limited, but is preferably 0.3 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, and still more preferably 0.75 to 5 parts by weight, based on the weight of the solid content, in terms of aluminum ions relative to 100 parts by weight of the component (A), from the viewpoint of not excessively increasing the viscosity of the paper strengthening agent and exhibiting an excellent paper strengthening effect.

[0059] The component (C) is an inorganic acid salt and has a function of weakening the electrostatic interaction between the components (A) and (B), and is used to achieve excellent storage stability of the paper strengthening agent.

[0060] Examples of the component (C) include nitrates such as ammonium nitrate, sodium nitrate, and potassium nitrate; nitrites such as ammonium nitrite, sodium nitrite, and potassium nitrite;

[0061] Secondary nitrates such as secondary ammonium nitrate, secondary sodium nitrate, secondary potassium nitrate;

[0062] Sulfates such as ammonium sulfate, sodium sulfate, potassium sulfate, ammonium hydrogen sulfate, sodium hydrogen sulfate, potassium hydrogen sulfate, etc.

[0063] Sulfites such as ammonium sulfite, sodium sulfite, potassium sulfite, etc.

[0064] Dithionites such as ammonium dithionite, sodium dithionite, potassium dithionite, etc.

[0065] Phosphates such as ammonium phosphate, sodium phosphate, potassium phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, diammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate;

[0066] Phosphites such as ammonium phosphite, sodium phosphite, potassium phosphite, diammonium hydrogen phosphite, disodium hydrogen phosphite, dipotassium hydrogen phosphite, ammonium dihydrogen phosphite, sodium dihydrogen phosphite, potassium dihydrogen phosphite, etc.;

[0067] Hypophosphites such as ammonium hypophosphite, sodium hypophosphite, potassium hypophosphite, diammonium hypophosphite, disodium hypophosphite, dipotassium hypophosphite, ammonium dihydrogen hypophosphite, sodium dihydrogen hypophosphite, potassium dihydrogen hypophosphite, etc. can be used alone or in combination of two or more. It should be noted that, for inorganic acid salts, hydrates can be used.

[0068] Among these (C) components, from the viewpoint of weakening the electrostatic interaction between the (A) component and the (B) component and exhibiting excellent storage stability of the paper strengthening agent, sulfates and / or phosphates are preferred, and it is more preferred to contain one or more selected from the group consisting of sodium phosphate, potassium phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, sodium sulfate, potassium sulfate, sodium hydrogen sulfate and potassium hydrogen sulfate, and it is further preferred to contain two or more selected from the above group.

[0069] The content of the component (C) is not particularly limited, but is preferably 1 to 70 parts by weight, more preferably 1 to 50 parts by weight, and even more preferably 1 to 30 parts by weight, based on the solid content weight, relative to 100 parts by weight of the component (A), from the viewpoint of reducing the electrostatic interaction between the components (A) and (B) and achieving excellent storage stability of the paper strengthening agent.

[0070] The (D) component is an inorganic acid. When the (D) component is added, the pH of the paper strengthening agent is lowered, and the anion components (e.g., substances derived from the (a3) ​​component in the (A) component) contained in the paper strengthening agent become difficult to dissociate (e.g., R-COOH→R-CO - +H +As a result, the electrostatic interaction between the (A) component and the (B) component is weakened, and the paper strength enhancer exhibits excellent storage stability. As the (D) component, for example, hydrochloric acid, nitric acid, nitrous acid, dithionite, sulfuric acid, sulfurous acid, dithionite, phosphoric acid, phosphorous acid, hypophosphorous acid, etc. can be cited. These can be used alone or in combination of two or more. Among them, sulfuric acid and phosphoric acid are preferred from the viewpoint of suppressing the pH rise of the paper strength enhancer and the excellent storage stability of the paper strength enhancer.

[0071] The content of the component (D) is not particularly limited, but is preferably 0.5 to 15 parts by weight, more preferably 1 to 12 parts by weight, and even more preferably 1 to 10 parts by weight, based on the solid content weight, relative to 100 parts by weight of the component (A), from the viewpoint of suppressing a rise in the pH of the paper reinforcing agent and exhibiting excellent storage stability of the paper reinforcing agent in addition to adjusting the pH of the paper reinforcing agent.

[0072] The paper strength enhancer of the present invention may also include organic acids such as citric acid, succinic acid, and oxalic acid; inorganic bases such as sodium hydroxide, potassium hydroxide, and calcium hydroxide; and additives such as urea, polysaccharides (such as starch), defoamers, antioxidants, polymerization inhibitors, and preservatives.

[0073] The paper strength enhancer of the present invention is obtained by mixing the components (A), (B), (C) and (D) and the above-mentioned additives as required at room temperature. In addition, water may be added for dilution. It should be noted that, regarding the component (A), two or more polymers produced under different compositions and conditions such as the types and / or usage amounts of the above-mentioned monomers may be mixed, and a material diluted with water in advance may also be used. In addition, these mixing methods and mixing orders are not particularly limited.

[0074] Regarding the paper strengthening agent obtained above, when the viscosity of the mixed solution just prepared (concentration 15 weight %, temperature: 25°C) is X1 mPa·s, and the viscosity of the mixed solution after being stored at a temperature of 60°C for 3 days (concentration 15 weight %, temperature: 25°C) is X2 mPa·s, 30≤X1≤30,000 and 0.8≤X2 / X1≤2. It should be noted that "just prepared" here means within 2 hours from the completion of preparation in order to stabilize the temperature of the obtained paper strengthening agent at 25°C.

[0075] (About viscosity X1)

[0076] If the viscosity X1 is less than 30 mPa·s, the paper strength agent dissolves in a large amount of water in the papermaking system and is easily lost during dehydration, making it difficult to exert the paper strength effect of the paper. In addition, if it exceeds 30,000 mPa·s, the following operations are likely to deteriorate: when the paper strength agent is diluted in a solvent such as water, it is difficult to mix uniformly, and in addition, it is difficult to send the paper strength agent by a pump or the like during paper production, and the desired amount of paper strength agent is not added to the pulp slurry. As a result, the paper strength effect of the paper is likely to deteriorate. In addition, from the same viewpoint, the viscosity X1 is preferably 100≤X1≤25,000, and more preferably 300≤X1≤20,000.

[0077] (About X2 / X1)

[0078] X2 / X1 is an indicator of the storage stability of the paper strength enhancer. If X2 / X1 exceeds 2, the viscosity continues to increase over time, so it is impossible to add the paper strength enhancer to the pulp slurry for long-term storage. From the same point of view, the viscosity X2 / X1 is preferably 0.8≤X2 / Xx≤1.8, and more preferably 0.8≤X2 / X1≤1.5.

[0079] As other physical properties of the paper strengthening agent of the present invention, from the viewpoint of maintaining excellent storage stability, the pH of an aqueous solution having a solid content concentration of 1 wt % at a temperature of 25° C. is preferably 2 to 3.5, more preferably 2 to 3, and even more preferably 2 to 2.5.

[0080] The paper of the present invention is obtained by using the above-mentioned paper strengthening agent, and its production method includes, for example, adding the paper strengthening agent to the raw material pulp slurry (hereinafter also referred to as internal addition) or coating it on the surface of the base paper, etc. It should be noted that the paper strengthening agent is preferably diluted with water to adjust the solid content concentration to 0.1 to 2.0% by weight.

[0081] When the paper strength agent is added to the raw material pulp slurry, the paper strength agent is added to the pulp slurry for papermaking. The amount of the paper strength agent used (converted as the solid content of the (A) component) is not particularly limited, and is about 0.01 to 4% by weight relative to the dry weight of the pulp. In addition, the type of pulp is not particularly limited, and examples thereof include chemical pulps such as broadleaf pulp (LBKP) and coniferous pulp (NBKP); mechanical pulps such as ground wood pulp (GP), refined groundwood pulp (RGP), and thermomechanical pulp (TMP); and waste paper pulps such as old corrugated cardboard. It should be noted that when the paper strength agent solution is added internally, in addition to the above, as a fixing agent, the following can be added: pH adjusters such as aluminum sulfate, sulfuric acid, and sodium hydroxide; papermaking chemicals such as sizing agents and wetting paper strength agents; and fillers such as talc, clay, kaolin, titanium dioxide, and calcium carbonate.

[0082] When applied to the surface of base paper, the paper strength enhancer is applied to the surface of base paper by various known methods. Here, the paper strength enhancer applied to the surface of base paper is referred to as a "coating liquid". The viscosity of the coating liquid is usually 1 to 40 mPa·s at 50°C. As the type of base paper, uncoated paper using wood cellulose fiber as a raw material can be used. The coating device is not particularly limited, and examples thereof include a rod coater, a knife coater, an air knife coater, a calender, a gate roll coater, a blade coater, a double-roll sizing press, a rod-type metering machine, and the like. In addition, the coating amount of the coating liquid (converted into solid content) is not particularly limited, and is usually 0.001 to 2 g / m 2 About 0.005 to 1 g / m 2 about.

[0083] The paper of the present invention can be used in various products, such as coated paper, newspaper paper, liners, cores, paper tubes, printing and writing paper, form paper, PPC paper, cup paper, inkjet paper, thermal paper, etc.

[0084] Example

[0085] The present invention is described below with reference to the following examples, but the present invention is not limited thereto. It should be noted that, unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight.

[0086] The abbreviations of the compounds are shown below.

[0087] AM: Acrylamide

[0088] DM: N, N-dimethylaminoethyl methacrylate

[0089] DML: N,N-dimethylaminoethyl methacrylate benzyl chloride

[0090] IA: itaconic acid

[0091] AA: Acrylic acid

[0092] SMAS: Sodium Methyl Allyl Sulfonate

[0093] DMAA: N,N-dimethylacrylamide

[0094] MBAA: N,N′-methylenebisacrylamide

[0095] TAF: 1,3,5-Triacryloylhexahydro-1,3,5-triazine

[0096] APS: Ammonium Persulfate

[0097] <Weight Average Molecular Weight of Component (A)>

[0098] The weight average molecular weight of the component (A) was measured by gel permeation chromatography (GPC) under the following measurement conditions.

[0099] Chromatographic columns: 1 PWXL and 2 GMPWXL guard columns manufactured by Tosoh Corporation

[0100] Eluent: Phosphate buffer (0.05 mol / L phosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) + 0.13 mol / L sodium dihydrogen phosphate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) aqueous solution, pH about 2.5)

[0101] Flow rate: 0.8ml / min

[0102] Temperature: 40℃

[0103] RI detector: Shodex RI-101 manufactured by Showa Denko K.K.

[0104] MALS detector: DAWN HELEOS-II manufactured by WYATT

[0105] Measurement sample: The sample was diluted with the above-mentioned eluent so that the polymer concentration became 0.1% and then measured.

[0106] <Viscosity of Component (A) and Paper Strengthening Agent>

[0107] The viscosity of the component (A) and the paper strengthening agent adjusted to a temperature of 25° C. was measured using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.).

[0108] <ph>

[0109] The pH of a sample of an aqueous solution of a paper strengthening agent having a concentration of 1% at a temperature of 25° C. was measured using a commercially available measuring instrument (product name: “pH METER F-14”, manufactured by Horiba, Ltd.).

[0110] Production Example 1

[0111] In a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen inlet tube and two dropping funnels, 162 parts of ion exchange water were added, and after nitrogen was passed through to remove oxygen in the reaction system, the reaction system was heated to 90°C. In the dropping funnel (1), 512 parts (92.5 mol%) of 50% AM, 30.6 parts (5 mol%) of DM, 10.1 parts (2 mol%) of IA, 2.5 parts (0.4 mol%) of SMAS, 15 parts of 62.5% sulfuric acid, 0.4 parts (0.1 mol%) of DMAA and 286 parts of ion exchange water were added, and the pH was adjusted to about 3.0 with sulfuric acid (monomer mixed solution). In the dropping funnel (2), 0.3 parts of APS and 180 parts of ion exchange water were added. Then, the catalyst in the system was added dropwise through the dropping funnel (2) over about 3 hours. At the same time, the monomer mixed solution in the dropping funnel (1) was added dropwise at a constant flow rate over about 3 hours. After the dropwise addition, 0.6 parts of APS and 10 parts of ion exchange water were added and the mixture was kept warm for 1 hour, and 853 parts of ion exchange water was added to obtain an aqueous solution of component (A-1) with a solid content concentration of 15%. The weight average molecular weight and viscosity of component (A-1) are shown in Table 1 (the same below).

[0112] Production Examples 2 to 17, Comparative Production Examples 1 to 3

[0113] With the composition shown in Table 1, synthesis was carried out in the same manner as in Production Example 1 to obtain an aqueous solution of the component (A) having a solid content concentration of 15%.

[0114]

Table 1

[0115]

[0116] Example 1

[0117] The following materials were mixed at room temperature for 15 minutes: 667 parts of an aqueous solution of the component (A-1) (100 parts of solid content), 17.5 parts of aluminum sulfate hexadecahydrate (1.5 parts in terms of weight of aluminum ions), 1.05 parts of sodium dihydrogen phosphate hydrate, 10 parts of sodium sulfate, 0.70 parts of phosphoric acid, and 2.25 parts of an aqueous sulfuric acid solution having a solid content concentration of 62.5% (1.4 parts of solid content), and then ion exchange water was added and mixed so that the solid content concentration became 15% to obtain a paper strengthening agent. The viscosity X1 (mPa·s) and pH of the paper strengthening agent are shown in Table 2 (the same below).

[0118] Examples 2 to 7, 9 to 27, Comparative Examples 1 to 9

[0119] With the composition shown in Table 2, the same procedure as in Example 1 was carried out to obtain a paper strengthening agent having a solid content concentration of 15%. It should be noted that the paper strengthening agents of Comparative Examples 4 and 5 had high viscosities immediately after synthesis, and the paper strengthening agent of Comparative Example 7 had a low molecular weight, so the following evaluation was not performed.

[0120] Example 8

[0121] The following materials are mixed at room temperature for 15 minutes: 667 parts of an aqueous solution of component (A-1) (100 parts of solid content), 94.4 parts of an aqueous solution of polyaluminum chloride (5.0 parts in terms of weight of aluminum ions), 2.1 parts of sodium dihydrogen phosphate hydrate, 30 parts of sodium sulfate, 1.4 parts of phosphoric acid and 13.8 parts of an aqueous solution of sulfuric acid having a solid content concentration of 62.5% (8.6 parts of solid content), and then ion exchange water is added and mixed so that the solid content concentration becomes 15% to obtain a paper strength enhancer.

[0122] Embodiment 28

[0123] The following materials are mixed at room temperature for 10 minutes: 333 parts of an aqueous solution of component (A-2) (50 parts of solid content), 333 parts of an aqueous solution of component (A-3) (50 parts of solid content), 17.5 parts of aluminum sulfate hexadecahydrate (1.5 parts in terms of weight conversion of aluminum ions), 1.05 parts of sodium dihydrogen phosphate hydrate, 10 parts of sodium sulfate, 0.7 parts of phosphoric acid and 2.25 parts of an aqueous sulfuric acid solution having a solid content concentration of 62.5% (1.4 parts of solid content), then ion exchange water is added and mixed so that the solid content concentration becomes 15% to obtain a paper strength enhancer.

[0124] <Storage stability>

[0125] Each paper strengthening agent was left to stand in a thermostat at 60°C for 3 days. The viscosity of each paper strengthening agent after adjusting the temperature to 25°C was measured, and the value was set as X2 (mpa·s), and X2 / X1 was calculated. The results are shown in Table 2.

[0126] <Papermaking Evaluation>

[0127] Ion exchange water was added for dilution so that each paper strengthening agent (A) shown in Table 2 had a solid content concentration of 1.0%. Then, the following papermaking evaluation was performed. It should be noted that the paper strengthening agents (Comparative Examples 3, 6, and 8) whose X2 / X1 exceeded 2 in the above storage stability test were not evaluated.

[0128] Used corrugated cardboard was beaten using a Niagara beater, and calcium chloride was added to the pulp slurry adjusted to a Canadian Standard Beating Fertilizer (CSF) of 350 mL to adjust the conductivity to 4.0 mS / cm. Aluminum sulfate was added to the slurry at a solid content of 0.5% relative to the weight of the solid content of the pulp slurry, and then the paper strength enhancer of Example 1 was added in an amount such that the solid content of component (A) was 0.5% relative to the weight of the solid content of the pulp slurry. The pH of each pulp slurry was adjusted to 6.5. Dewatering was performed using a TAPPI paper machine at 5 kg / cm 2 Pressing was performed for 2 minutes to produce paper so that the weight per unit area became 150 g / m 2 . Then, the paper was dried at 105°C for 4 minutes using a rotary dryer, and the paper was humidified at 23°C and 50% for 24 hours to measure the bursting strength. The paper strengthening agents of Examples 2 to 24 and Comparative Examples 1 to 2 were also evaluated in the same manner. It should be noted that the conductivity, filtered water volume, and bursting strength were measured by the following methods. The results are shown in Table 2.

[0129] <Electrical conductivity>

[0130] The measurement was performed using pH / COND METER D-54 (manufactured by Horiba, Ltd.).

[0131] <Filtered water volume>

[0132] Canadian Standard Freeness (CSF) was used and measured according to J1S P 8121.

[0133] <Specific Bursting Strength>

[0134] The paper obtained above was used to measure the specific bursting strength (kPa·m 2 / g).

[0135]

Table 2

[0136]

[0137] *1: It is expressed as parts by weight of aluminum ions relative to 100 parts by weight (solid content) of the component (A).

[0138] *2: Indicated by parts by weight of the components (C) and (D) relative to 100 parts by weight (solid content) of the component (A).< / ph>

Claims

1. A paper strengthening agent, which is a mixed solution comprising a (meth)acrylamide polymer (A), a water-soluble aluminum compound (B), an inorganic acid salt (C) and an inorganic acid (D), in, The (meth)acrylamide polymer (A) comprises (meth)acrylamide (a1), a polymerizable monomer having a cationic group (a2), a polymerizable monomer having an anionic group (a3) ​​and a crosslinking monomer (a4) as reaction components, and the component (B) is not included in the inorganic acid salt (C); The viscosity of the mixed solution with a solid content concentration of 15% by weight and a temperature of 25°C just prepared is defined as X. 1 mPa·s, and the viscosity of the mixed solution at a solid content concentration of 15% by weight and a temperature of 25°C after being stored at a temperature of 60°C for 3 days is defined as X 2 mPa·s, 30≤X 1 ≤30,000 and 0.8≤X 2 / X 1 ≤2.

2. The paper strengthening agent according to claim 1, in, The molar ratio of the reaction components is: 55 mol% to 98 mol% of component (a1), 0.5 mol% to 20 mol% of component (a2), 0.5 mol% to 20 mol% of component (a3), and 0.002 mol% to 2 mol% of component (a4).

3. The paper strengthening agent according to claim 1 or 2, in, The component (B) is aluminum sulfate and / or its hydrate.

4. The paper strengthening agent according to claim 1 or 2, in, The content of the component (B) is 0.3 to 20 parts by weight as an amount of aluminum ions based on the solid content weight relative to 100 parts by weight of the component (A).

5. The paper strengthening agent according to claim 1 or 2, in, The component (C) contains one or more selected from the group consisting of sodium phosphate, potassium phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, sodium sulfate, potassium sulfate, sodium hydrogen sulfate, and potassium hydrogen sulfate.

6. The paper strengthening agent according to claim 1 or 2, in, The content of the component (C) is 1 to 70 parts by weight based on 100 parts by weight of the component (A) in terms of solid content.

7. The paper strengthening agent according to claim 1 or 2, in, The component (D) is sulfuric acid and / or phosphoric acid.

8. The paper strengthening agent according to claim 1 or 2, wherein the pH of an aqueous solution thereof having a solid content concentration of 1 wt% at a temperature of 25°C is 2 to 3.

5. 9 . Paper obtained by using the paper strengthening agent according to claim 1 .